2022
DOI: 10.3390/biology11071018
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Rapid Reverse Transcription-Recombinase Polymerase Amplification Couple Nucleic Acid Lateral Flow Method for Detecting Porcine Epidemic Diarrhoea Virus

Abstract: Porcine epidemic diarrhea virus (PEDV) infection is an important acute diarrheal disease of swine that results in economic and industrial losses worldwide. The clinical manifestations in infected piglets are severe diarrhea, dehydration with milk curd indigestion, leading to death. The diagnosis of PEDV is essential for monitoring and managing the disease. PEDV can be detected and identified by serology and the nucleic acid of the virus in clinical samples. Therefore, a novel isothermal amplification and detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The reverse transcriptase polymerase chain reaction method was used to validate the results. The study results showed that the RT-RPA-NALF can detect the amplicon virus within 25 min at a temperature of 42 °C, with a sP and sN of 100% and 95.65%, respectively, with a 98.33% coincidence rate ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reverse transcriptase polymerase chain reaction method was used to validate the results. The study results showed that the RT-RPA-NALF can detect the amplicon virus within 25 min at a temperature of 42 °C, with a sP and sN of 100% and 95.65%, respectively, with a 98.33% coincidence rate ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, numerous techniques for detecting PEDV have been reported, including conventional virus isolation (Valkó et al 2019 ), enzyme-linked immune sorbent (ELISA) (Gerber et al 2014 ), and molecular biological techniques (Kim et al 2007 ). Virus isolation and identification is a laborious process that takes a lot of time and necessitates specialized equipment and personnel; ELISA has been widely used to detect the level of antibodies in serum, but it was not a good choice for early diagnosis of viral infection as antibody generation required a few days, it was also laborious and time-consuming (Pewlaoo et al 2022 ; Wang et al 2020 ). Several molecular biological techniques commonly employed for PEDV diagnostics are quantitative polymerase chain reaction (qPCR) (Pan et al 2020 ), recombinase polymerase amplification (RPA) (Li et al 2021b ), and loop-mediated isothermal amplification (LAMP) (Yu et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%